Szabadságvesztés-büntetésüket töltők lakóhelyeinek térbeni elhelyezkedése Budapesten - Ladányi, János (Tér és Társadalom, 1991)
In this study, the author summarizes the results of research into the spatial segregation of imprisoned offenders in the capital city of Hungary. Using data on the place of residence of imprisoned offenders in 1979 in Budapest, it also assesses police claims that there are areas of Budapest where there are high concentrations of offenders. One focus is a comparison of these concentrations of offenders with the most disadvantaged group in Hungarian society, the gypsies. The sample of offenders studied in this project (2,284 individuals) consisted of those over 18 years of age serving the sentences in Hungary on the 31 October 1979 and gave Budapest as their permanent or temporary address (but not those living in workers' hostels or reformatory schools). The initial analysis of the spatial distribution of the imprisoned offenders involved their grouping, and then their plotting on a detailed map of Budapest showing each house and plot. The different groups of offenders were plotted with different colour. In the first step, the different - colour dots were added by census tracts (there were 490 such tracts in Budapest in 1980), and the resulting data, together with some other census data, were processed by computer. The greatest advantage of the above plotting method was that this way, not only the distribution of the investigated phenomenon by census tracts could be revealed, but also the overlapping, or small concentrations became visible. In the first step, the distribution of the population in question was investigated in those dimensions which facilitated the comparison with the capital city's average population. According to the data, the imprisoned offenders are much less educated than the average population of Budapest. This difference is even more striking if we take into consideration that the imprisoned offenders are usually younger, and the younger generations usually have higher educational levei. In the case of imprisoned offenders, 60% finished 8 grades of the elementary school as a maximum, and if they participated in secondary education at alt, that was vocational training, and only every 50th of them has some sort of higher education. As opposed to this, only 50 % of the inhabitants of Budapest, who are usually older, have maximum 8 grades of elementary education, if they participated in secondary education, that was more likely secondary grammar school than vocational training, and every 8th of them have some sore of diploma. When examining the residential segregation of imprisoned offenders, the author first summarizes the segregational patterns of different social and ethnic groups. The author indicates that the spatial segregation of these different groups is characterízed by the contrast between the large concentration of high-status groups in parts of Buda and the dispersed but clearly definable small areas of low-status groups on the Pest-side of the capital. The area where gypsies live in the slums of inner Pest, however, forms a large, coherent area. The spatial distribution of imprisoned offenders is more even, except that they tend to be over-represented in the inner, slum areas of Pest and under-represented in the high-status parts of Buda. When examining the segregational indexes of the different groups of imprisoned offenders created by their educational levei, the number of imprisonments and the time spent in prison it could be concluded, that the data on imprisoned offenders in Budapest do not support the view that there is a mass criminal subculture living in a certain part or parts of the city. Furthermore, in those parts of the city which are portrayed as „criminal areas" in police reports, such as the inner city slum areas of Pest, the proportion of imprisoned people is usually no higher than the proportion one would expect given the low status of the people living in these areas.